Study of the antimicrobial and fungicidal activity of thiotriazoline and decamethoxinum as a potentially new model mixture for use of the oral mucosa - Kucherenko, L. I.; Bielenichev, I. F.; Chonka, О. О.; Moriak, Z. B.; Portna, O. O.; Кучеренко, Людмила Іванівна; Бєленічев, Ігор Федорович; Чонка, Олена Олегівна; Моряк, Зінаїда Броніславівна; Портна, Олена Олексіївна; Кучеренко, Л. И.; Беленичев, И. Ф.; et al. (Запорізький державний медичний університет, 2020)
Today, diseases caused by pathogenic bacteria are the most dangerous, as they can not only affect the quality of human life, but also lead to death. According to the WHO, pathogenic bacteria namely, mycoses affect from 1/5 to 1/3 of the world’s population, more than a third (37.8 %) of them cause yeast-like (Candida). Over the past 20 years, there has been a 15-fold increase in the frequency of infectious inflammatory diseases of candidiasis etiology. After examining the range of drugs on the pharmaceutical market of Ukraine and abroad, it was found that the following drugs of foreign origin are currently used for the treatment of these diseases: Methyluracil (Lekhim, Ukraine), Solkoseril (Birsfelden, Switzerland), Mexidol (PHARMASOFT, Moscow, RF). Based on the above it is seen that the range of drugs for the treatment of oral mucosa diseases is limited. All of the above shows the need for the creation of a new domestic drug exhibiting antimicrobial, fungicidal, reparative activity. The aim of our work is to create a new drug based on the model mixture of Thiotriazoline and Decamethoxinum, which exhibit antimicrobial, fungicidal, repertoire activity. Materials and methods. Thiotriazoline, decamethoxinum, model mixture. The studies were carried out by agar diffusion (well method) to study antimicrobial activity. Model mixtures with decamethoxinum were made from 0.5 to 5.0 mg; thiotriazoline – 200 mg. Antimicrobial activity of these model mixtures was carried out. Results. The model mixture of thiotriazoline and decamethoxinum in antimicrobial and fungicidal action was significantly superior to decamethoxinum by 54 % in the degree of growth inhibition of S. aureus, by 120 % in the degree of growth inhibition of E. coli, by 57 % in the degree of growth inhibition of P. aeruginosa, and by 108 % in the degree of growth retardation of C. albicans at 106 CFU/ml of medium. Conclusion. The model mixture of thiotriazoline and decamethoxinum exhibits high antimicrobial and fungicidal activity. Захворювання, які викликають хвороботворні бактерії, – найнебезпечніші, оскільки здатні не тільки впливати на якість життя людини, але і призводити до летальних наслідків. Згідно з даними ВООЗ, хвороботворними бактеріями, як-от мікозами, уражено від 1/5 до 1/3 населення планети, у понад третини (37,8 %) з них збудником захворювання є дріжджоподібні гриби роду Candida. За останні 20 років фахівці спостерігають підвищення в 15 разів частоти інфекційних запальних захворювань кандидозної етіології. Вивчивши асортимент лікарських препаратів на фармацевтичному ринку України та за кордоном, установили: для лікування цих захворювань використовують лікарський засіб Метилурацил (Лекхім, Україна) та препарати іноземного виробництва Соркосерил (Бірсфельден, Швейцарія), Мексидол (ФАРМАСОФТ, м. Москва, РФ). Асортимент лікарських засобів для лікування захворювань слизової оболонки порожнини рота – обмежений. Отже, є потреба у створенні нового вітчизняного препарату, що проявлятиме антимікробну, фунгіцидну, репаративну активність. Мета роботи – створення нового лікарського засобу на основі модельної комбінації тіотріазоліну й декаметоксину, що проявлятиме антимікробну, фунгіцидну, репаративну активність. Матеріали та методи. Тіотріазолін, декаметоксин, модельна суміш тіотріазоліну та декаметоксину. Дослідження антимікробної активності здійснили методом дифузії в агар (метод колодязів). Виготовили модельні суміші з вмістом декаметоксину від 0,5 до 5,0 мг; тіотріазоліну – 200 мг. Перевірена антимікробна активність цих модельних сумішей. Результати. Модельна суміш тіотріазоліну та декаметоксину за силою антимікробної та фунгіцидної дії вірогідно перевершувала декаметоксин на 54 % за ступенем затримки росту S. aureus, на 120 % – за ступенем затримки росту E. coli, на 57 % – за ступенем затримки росту P. aeruginosa, на 108 % – за ступенем затримки росту C. albicans при 106 КУО/мл середовища. Висновки. Модельна суміш тіотріазоліну та декаметоксину має високу антимікробну, фунгіцидну, репаративну активність. Сегодня болезни, вызываемые болезнетворными бактериями, – самые опасные, так как они способны не только влиять на качество жизни человека, но и привести к смертельному исходу. По данным ВОЗ, болезнетворными бактериями, а именно микозами, поражено от 1/5 до 1/3 населения Земли, более чем у трети (37,8 %) из них возбудителем заболевания являются дрожжеподобные грибы рода Candida. За последние 20 лет отмечено повышение в 15 раз частоты инфекционных воспалительных заболеваний кандидозной этиологии. Изучив ассортимент лекарственных препаратов на фармацевтическом рынке Украины и за рубежом, установили: для лечения данных заболеваний используют Метилурацил (Лекхим, Украина) и препараты иностранного производства Соркосерил (Бирсфельден, Швейцария), Мексидол (ФАРМАСОФТ, г. Москва, РФ). Ассортимент лекарственных средств для лечения заболеваний слизистой оболочки полости рта – ограничен. Следовательно, возникла необходимость создать новое отечественное лекарственное средство, проявляющее антимикробную, фунгицидную, репаративную активность. Цель работы – создание нового лекарственного средства на основе модельной комбинации тиотриазолина и декаметоксина, проявляющего антимикробную, фунгицидную, репаративную активность. Материалы и методы. Тиотриазолин, декаметоксин, модельная смесь тиотриазолина и декаметоксина. Противомикробная активность исследована методом диффузии в агар (метод колодцев). Изготовлены модельные смеси с содержанием декаметоксина от 0,5 до 5,0 мг; тиотриазолина – 200 мг. Проверена противомикробная активность данных модельных смесей. Результаты. Модельная смесь тиотриазолина и декаметоксина по силе антимикробного и фунгицидного действия достоверно превосходила декаметоксин на 54 % по степени задержки роста S. aureus, на 120 % – по степени задержки роста E. coli, на 57 % – по степени задержки роста P. aeruginosa и на 108 % – по степени задержки роста C. albicans при 106 КОЕ/мл среды. Выводы. Модельная смесь тиотриазолина и декаметоксина проявляет высокую антимикробную, фунгицидную активность.
Вивчення протимікробної та фунгіцидної активності тіотріазоліну та декаметоксину як потенційно нової модельної суміші для застосування при захворюваннях слизової оболонки порожнини рота
Изучение противомикробной и фунгицидной активности тиотриазолина и декаметоксина как потенциально новой модельной смеси для применения при заболеваниях слизистой оболочки полости рта
Кучеренко Л. І. - ORCID ID: 0000-0003-2229-0232; Бєленічев І. Ф. - ORCID ID: 0000-0003-1273-5314; Чонка О. О. - ORCID ID: 0000-0002-6793-2668; Моряк З. Б. - ORCID ID: 0000-0001-9416-9517; Портна О. О -ORCID ID: 0000-0002-4752-1888.
Keywords: oral mucosa; pathological processes; model mixture; thiotriazoline; decamethoxinum; захворювання слизової оболонки порожнини рота; модельна суміш; декаметоксин; тіотріазолін; заболевания слизистой оболочки полости рта; модельная смесь; декаметоксин; тиотриазолин